2012
DOI: 10.1103/physrevb.85.075423
|View full text |Cite
|
Sign up to set email alerts
|

Electrically tunable band gap in silicene

Abstract: We report calculations of the electronic structure of silicene and the stability of its weakly buckled honeycomb lattice in an external electric field oriented perpendicular to the monolayer of Si atoms. The electric field produces a tunable band gap in the Dirac-type electronic spectrum, the gap being suppressed by a factor of about eight by the high polarizability of the system. At low electric fields, the interplay between this tunable band gap, which is specific to electrons on a honeycomb lattice, and the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

39
883
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,096 publications
(925 citation statements)
references
References 27 publications
39
883
1
2
Order By: Relevance
“…The electronic structure of silicene in a perpendicular electric field has been addressed in Ref. [8] and the results of Drummond and coworkers [9] suggest that variation of the electric field with respect to the strength of the spin-orbit coupling induces a transition between a topological and a band insulator.…”
Section: Introductionmentioning
confidence: 99%
“…The electronic structure of silicene in a perpendicular electric field has been addressed in Ref. [8] and the results of Drummond and coworkers [9] suggest that variation of the electric field with respect to the strength of the spin-orbit coupling induces a transition between a topological and a band insulator.…”
Section: Introductionmentioning
confidence: 99%
“…51 Recent theoretical studies have revealed several remarkable features of silicene such as a large spin-orbit gap at the Dirac point, 52 experimentally accessible quantum spin Hall effect, 53 transition from a topological insulating phase to a band insulator that can be induced by an electric field 54 and electrically tunable band gap. 55 In addition to unique insulator phases such as quantum spin Hall, quantum anomalous Hall and band insulator phases, the emergence of valley-polarized metal phase was also reported very recently. 56 It appears that silicene will be a possible graphene replacement not only due to its graphene-like features but also because of its compatibility to existing silicon-based electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…This has been termed a valley-spin-polarized metal (VSPM). For (E z /E c ) >1 (for example, the case(c) where the ratio (E z /E c ) is 1.44), the spectrum becomes fully gapped again but the system is a band insulator albeit with unusual chiral properties [18].…”
Section: B the Low-energy Excitation Spectrummentioning
confidence: 99%